Paraguay : 2007 Article IV Consultation and Second and Third Reviews Under the Stand-By Arrangement; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Paraguay. (IMF Staff Country Reports; Country Report, 2008)
Raising growth on a sustainable basis and addressing widespread poverty are the main challenges for Paraguay. The macroeconomic program for 2007 aims at raising growth and reducing inflation. IMF staff recommends that the next Article IV Consultation continues within the 24-month cycle, and supports completion of the second and third Stand-by Arrangement (SBA) reviews. After the 2002 financial crisis, growth has rebounded to almost twice its long-term average, per capita income surged to its highest level in 8 years, and extreme poverty has been reduced by almost one third.